Quantified Blood Loss: An Alternative Method in Correlating Change in Predelivery and Postdelivery Hematocrit [330]. (May 2015) - Williams, Brittney A.; Seidel, Sharon L.; Jackson, Jessica Rose; Amin, Raid; Bakker, Blakele N.; DeCesare, Julie Zemaitis
Abstract : INTRODUCTION: Obstetric hemorrhage continues to contribute to significant maternal morbidity and mortality in the United States and worldwide. In the state of Florida, hemorrhage accounted for 15% of pregnancy-related deaths between 2005 and 2009. Few studies have been done to access the correlation between estimated blood loss and quantified blood loss to the change in predelivery and postdelivery hematocrit. Our study prospectively examines blood loss using quantification methods as opposed to visual methods in hopes of having an alternative method to correlate the change in hematocrit and also with diagnosing postpartum hemorrhage sooner in the postpartum course. METHOD: A prospective observational study was conducted by reviewing the obstetric records for patients with vaginal and cesarean deliveries from March 2014 to July 2014. Inclusion criteria are patients delivered at the Sacred Heart Hospital. Exclusion criteria are patients transferred to Sacred Heart Hospital during the postpartum period, data sheets without patient-identifying information, and patients in whom quantitative blood loss were not performed. Quantified blood loss was performed using weight-based measurements. RESULTS: During the 4-month period, a total of 54 patients was included in the study that had both a visually estimated blood loss and quantified blood loss. In comparing estimated blood loss and quantitative blood loss, they are significantly correlated by Pearson test for correlation with a r =0.58438 and P <.001. In correlating estimated blood loss with change in hematocrit, there is a weak correlation with r =0.18856; however, it is not statistically significant with a P <.173. Quantitative blood loss and change in hematocrit are well correlated with r =0.34527 and P <.009. CONCLUSION: Quantitative blood loss provides an alternative method to correlate predelivery and postdelivery change in hematocrit and does so with greater correlation than estimated blood loss. Utilizing quantitative blood loss can heighten awareness of postpartum hemorrhage and lead to more timely interventions in managing postpartum hemorrhage.